The Role of The Pharmacist in The Success of Tuberculosis (Tb) Treatment in Jeneponto Regency - Sitti Hartina; Elly Wahyudin; Hasyim Kasim (Universitas Batanghari Jambi, 2023)
Tuberculosis (TB) is an infectious disease caused by the bacterium called Mycobacterium tuberculosis leading to the inflammation of the lung parenchyma. This study aims to determine the effect of counseling on drugs and disease on TB patients and Medication Supervisors (PMO) as well as to determine the effect of PMO in increasing TB patient compliance with monitoring of each respondent. This study used two instruments, the first instrument was the TB-P10 instrument to measure the knowledge of respondents and PMO with pre and post-monitoring. The second instrument was MARS-5, given to the respondent and PMO to see how the respondent's compliance after therapy. Based on the results of the analysis of the paired t-test, it is known that the significance so it can be concluded that there is an average difference between the pre-test and post-test knowledge levels of PMO, which means that there is an effect of pharmacist counseling interventions to respondents and PMO in improving their knowledge. Meanwhile, the performance of PMO in increasing patient medication compliance showed a good performance with 48 patients (96%) who adhered to taking medication, while the poor performance was 2 patients who did not adhere to taking medication (4%). Based on the results of the analysis of the Wilcoxon test, it is known that the significanc, so it can be concluded that there is a relationship between PMO performance on patient medication compliance with clinical outcomes in the presence of patient weight gain and negative final of AFB results.